CATION EXCHANGE REACTIONS CONTROLLING DESORPTION OF 90Sr2+ FROM COARSE-GRAINED CONTAMINATED SEDIMENTS AT THE HANFORD SITE, WASHINGTON - McKinley J.P.; Zachara J.M.; Smith S.C.; Liu C. (My University, 2007)
Nuclear waste that bore 90Sr2+ was accidentally leaked into the vadose zone at the Hanford site, and was immobilized at relatively shallow depths in sediments containing little apparent clay or silt-sized components. Sr2+, 90Sr2+, Mg2+, and Ca2+ was desorbed and total inorganic carbon concentration was monitored during the equilibration of this sediment with varying concentrations of Na+, Ca2+. A cation exchange model previously developed for similar sediments was applied to these results as a predictor of final solution compositions. The model included binary exchange reactions for the four operant cations and an equilibrium dissolution/precipitation reaction for calcite. The model successfully predicted the desorption data. The contaminated sediment was also examined using digital autoradiography, a sensitive tool for imaging the distribution of radioactivity. The exchanger phase containing 90Sr was found to consist of smectite formed from weathering of mesostasis glass in basaltic lithic fragments. These clasts are a significant component of Hanford formation sands. The relatively small but significant cation exchange capacity of these sediments was thus a consequence of reaction with physically sequestered clays in sediment that contained essentially no fine-grained material. The nature of this exchange component explained the relatively slow (scale of days) evolution of desorption solutions. The experimental and model results indicated that there is little risk of migration of 90Sr2+ to the water table. © 2006 Elsevier Inc. All rights reserved.